Drug‐induced increase in lysobisphosphatidic acid reduces the cholesterol overload in Niemann–Pick type C cells and mice. (22nd May 2019) - Moreau, Dimitri; Vacca, Fabrizio; Vossio, Stefania; Scott, Cameron; Colaco, Alexandria; Paz Montoya, Jonathan; Ferguson, Charles; Damme, Markus; Moniatte, Marc; Parton, Robert G; Platt, Frances M; Gruenberg, Jean
Abstract: Most cells acquire cholesterol by endocytosis of circulating low‐density lipoproteins (LDLs). After cholesteryl ester de‐esterification in endosomes, free cholesterol is redistributed to intracellular membranes via unclear mechanisms. Our previous work suggested that the unconventional phospholipid lysobisphosphatidic acid (LBPA) may play a role in modulating the cholesterol flux through endosomes. In this study, we used the Prestwick library of FDA‐approved compounds in a high‐content, image‐based screen of the endosomal lipids, lysobisphosphatidic acid and LDL‐derived cholesterol. We report that thioperamide maleate, an inverse agonist of the histamine H3 receptor HRH3, increases highly selectively the levels of lysobisphosphatidic acid, without affecting any endosomal protein or function that we tested. Our data also show that thioperamide significantly reduces the endosome cholesterol overload in fibroblasts from patients with the cholesterol storage disorder Niemann–Pick type C (NPC), as well as in liver of Npc1 −/− mice. We conclude that LBPA controls endosomal cholesterol mobilization and export to cellular destinations, perhaps by fluidifying or buffering cholesterol in endosomal membranes, and that thioperamide has repurposing potential for the treatment of NPC. Synopsis: A high content screen identifies compounds that modulate the levels of the late endosomal phospholipid lysobisphosphatidic acid (LBPA). LBPA controls the mobilization and export of cholesterol from endosomal membranes, perhaps by changing their cholesterol buffering capacity. Thioperamide, an inverse agonist of the histamine H3 receptor identified in a high content screen for compounds that affect endosomal lipids, selectively raises the levels of lysobisphosphatidic acid (LBPA). Thioperamide does not affect other endosomal proteins or endosomal functions. Thioperamide reduces the cholesterol overload in fibroblasts from patients with the cholesterol storage disorder Niemann‐Pick type C (NPC), as well as in the liver of Npc1 −/− mice. Abstract : Thioperamide selectively increases the levels of the endosomal phospholipid lysobisphosphatidic acid and reduces the endosomal cholesterol overload in Niemann‐Pick type C patient fibroblasts or the livers of Npc1 ‐deficient mice.